Analisis Simulasi Antena MIMO 4 4 Susunan Persegi dan Sirkular pada Frekuensi 15 GHz - Fajar Wahyu Ardianto; Nachwan Mufti A.; Budi Syihabuddin (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
One of the frequency that becomes 5G candidate is 15 GHz. Utilizing high frequency can produce wider bandwidth but susceptible to reflection or scattering and it causes multipath fading. MIMO is believed to be able to fix the problem. Beside that, utilizing high frequency causes the antenna dimension become smaller so 5G technology requires an easily integrated antenna. Therefore, microstrip antenna becomes a suitable candidate for this technology. This paper discusses about rectangular and circular patch analysis for 5G radio access made into 1×2 array and added T-slotted patch to produce wider bandwidth and arranged four elements to form MIMO to reduce effects due to the multipath fading. The results show that the addition of a slotted-patch antenna in rectangular patch produces 2.3 GHz bandwidth in frequency range 14.3 – 15.6 GHz with minimal return loss of -23.91 dB, while in circular patch produces 2.8 GHz bandwidth in frequency range 14.5 – 17.3 GHz with minimal return loss of -19.19 dB. Maximum gain of rectangular and circular antennas are 10.30 dB and 9.95 dB, respectively, while mutual coupling values are -24.75 dB and -24.26 dB. Both patches produce same radiation patterns which are unidirectional and polarized linearly.